Degradable plastic production from low-quality rice - Chatporn Nankongnaeb; Xue, Wenchao; Chongrak Polprasert; Bora, Tanujjal; Asian Institute of Technology Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2021)
The low-cost production procedure of biodegradable plastic which made from low-quality rice was buildup. The estimated of low-cost production is about 64,000 THB per ton which is already included the selling and the administrative expenses. The estimated cost of production is not equal for each year. Because it depends on the change in raw material prices in the market each year. To improve stretchability of the biodegradable plastic, the producer needs to concern more about adjusting the ratio design between precursor and additives. Adding amylose content for the rice flour is also needs to be concerned as it tends to increase the levels of roughness, hardness, dryness of the product from the rice flour and decrease the product{u2019}s swelling power at the meantime. The researcher should also concern about the percentage of damaged starch content. The rice with damaged starch content by 3 - 4% are tend to be more stable and structured. After monitoring the biodegradability of the biodegradable plastic from low-quality rice and high-quality rice, it was found that biodegradable plastic which made from high-quality rice with ratio design no.2 (Starch : Sorbitol : Glycerol, 5 : 3 : 2) spent least time (4 days) to degrade when landfilled in the soil. All of the biodegradable plastic were degraded in the soil within 9 days of landfilling. From this study, the ratio design no.2 has highest amount of sorbitol compare to the other 2 ratio designs. Thus, from the experiment, sorbitol tends to increases the biodegradability of biodegradable plastic produced from starch of the rice.
A research study submitted in partial fulfillment of the requirements for the degree of Master in Marine Plastics Abatement
Research studies project report (M.) - Asian Institute of Technology, 2021
Keywords: Plastics -- Environmental aspects -- Thailand; Biopolymers -- Thailand; Rice -- Plastic properties